Behavioural Profile of Young Soccer Players in Social Projects - Pelicer, Flavio Roberto; Lope, Jose Carlos; Miyazaki, Maria Cristina de Oliveira Santos; Verardi, Carlos Eduardo Lopes [UNESP]; Nagamine, Kazuo Kawano (Federacion Espanola Asoc Docentes Educacion Fisica-feadef, 2023)
Studies report important positive outcomes of sports activities for youth, both the physical and psychological level and using for to taking children out of the streets or as an educational tool. The objective of the present study was to analyse the behaviour of young soccer players in social projects. Participants were 127 young male soccer players participate in social projects in two cities located in the State of Sao Paulo, Brazil, with mean age of 12.93 (+/- 1.46). To analyse the behaviour profile the Child Behaviour Checklist (CBCL) for ages 6-8 and the Youth Self-Report (YSR) for ages 11-18 were used, and participant ' s scores were analysed, compared and classified into clinical and non-clinical. In the analysis of the scores, borderline scores were included in the clinical range (t escore = 65 for clinical range). Among the behaviour variables observed in the inventories, the results indicate that over 91% of the participants were classified as '' Non-Clinical ''. Data suggests that the practice of soccer in social projects offers a protection mechanism for the overall psychological functioning of the participants in the evaluated scales. Furthermore, they support literature data, which reports benefits in mental health and the behaviour of youth involved in sports activities
Keywords: Mental Health; Adolescent Behaviour; Soccer; Public Health; Psychology Sports